MODERN LIFESTYLE AND ITS IMPACT ON THE ULCERATIVE COLITIS INCIDENCE - G. R. Bikbavova; M. A. Livzan; V. I. Sovalkin; D. V. Turchaninov; O. E. Lopatina; T. V. Tretyakova; A. P. Ahramovich; T. S. Gordienko (Архивъ внутренней медицины)
The aim of the study. To assess the significance of surrogate markers of the «hygienic hypothesis», the «old friends theory» and the hypothesis of «depletion of biomes» in the development of ulcerative colitis among the population of Western Siberia.Materials and methods: an active survey (interviewing) of 81 patients with ulcerative colitis and 39 healthy respondents was conducted. The main surrogate markers of the «hygienic theory», the hypotheses of «old friends» and «depletion of biomes» were studied: past infestations, pets in childhood, use of antibiotics, breastfeeding, family size (number of siblings), attendance at pre-school institutions, accommodation in a dormitory while studying, accommodation in a city or a village, type of drinking water supply and the type of water respondents use for drinking; in the framework of the «biome depletion» theory, in addition to the markers listed above, a sugar consumption rate was assessed. Consumption of simple carbohydrates was calculated based on the number of cups of tea and/or coffee drunk per week and the number of teaspoons or cubes of sugar that the respondent puts in one cup.Results. Among the indirect markers of the «hygiene hypothesis» and the theory of «old friends» examined, only one effect the risk of ulcerative colitis among the population of the Omsk region — visiting preschool institutions (2I = 4,59, p <0,05). Of the indirect signs of the «biome depletion» hypothesis examined, significant differences were found in the amount of simple carbohydrates consumed: patients with ulcerative colitis consumed more sugar with tea and/or coffee in the period before the first signs of the disease than healthy respondents (U = 1214,0; Z = 2,0; p = 0,04).Conclusion. In our study, the statistical significance of such factors as rare visits to kindergartens and the consumption of large amount of sugar by patients with ulcerative colitis in the period before the onset of the disease in comparison with healthy respondents was demonstrated.